1990
DOI: 10.1128/jcm.28.8.1704-1707.1990
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Captia enzyme immunoassays for detection of immunoglobulins G and M to Treponema pallidum in syphilis

Abstract: Two new enzyme-linked immunosorbent assays (ELISA), one for the measurement of immunoglobulin G (IgG) (Captia Syphilis-G) and one for the measurement of IgM (Captia Syphilis-M), were evaluated for detecting antibodies to Treponema pallidum. Serum samples from 169 patients, 96 with various stages of untreated syphilis, 63 with treated syphilis, and 10 who were noninfected, were investigated. Ail sera were also examined by traditional treponemal and cardiolipin tests and by the fluorescent treponemal antibody ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
5

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(36 citation statements)
references
References 22 publications
2
28
1
5
Order By: Relevance
“…The sensitivity of the competitive EIA for both treated and untreated syphilis is similar to that reported for other EIAs for T. pallidum. Lefevre et al (10) obtained 100% sensitivity with the Captia Syphilis G assay, similar to those obtained with TPHA and the FTA-abs test, at all stages of the disease except primary syphilis, in which the EIA may have lower sensitivity. We found that the BioElisa Syphilis detected all five cases of primary syphilis, whereas the TPHA results were still at or below threshold values.…”
Section: Discussionsupporting
confidence: 58%
“…The sensitivity of the competitive EIA for both treated and untreated syphilis is similar to that reported for other EIAs for T. pallidum. Lefevre et al (10) obtained 100% sensitivity with the Captia Syphilis G assay, similar to those obtained with TPHA and the FTA-abs test, at all stages of the disease except primary syphilis, in which the EIA may have lower sensitivity. We found that the BioElisa Syphilis detected all five cases of primary syphilis, whereas the TPHA results were still at or below threshold values.…”
Section: Discussionsupporting
confidence: 58%
“…Lefevre and colleagues showed that for the detection of anti‐TP antibody for each stage of syphilis, anti‐TP IgM was positive for 16/17 cases of primary syphilis, 11/13 of secondary syphilis, 9/14 of early latent syphilis, and 0/33 of late latent syphilis. On the other hand, anti‐TP IgG was positive for 14/17, 13/13, 14/14, and 33/33 of samples at each stage …”
Section: Introductionmentioning
confidence: 96%
“…2, 3) for G15, five samples (nos. [1][2][3][4]11) for M47, and three samples (nos. 1,2,22) for S42 had a Cl of < 1.0.…”
Section: Evaluation Of Human Sera Using Recombinant G17 G15 M47 Anmentioning
confidence: 99%
“…Clinical diagnostics issues related to syphilis and the latest methods for the detection of syphilis antibodies in human blood by immunoassay, immunoblotting, and polymerase chain reaction (PCR) have been reviewed briefly (1). Among the existing immunological methods, we can distinguish two common confirmatory treponemal tests: the agglutination format such as the T. pallidum hemagglutination assay (TPHA) (2) and the microhemagglutination assay (MHA-Tp), and the immunostaining analysis by fluorescent treponemal antibody adsorption test (FTA-ABS) (3). Although the FTA-ABS is tedious to perform and timeconsuming, it is considered to be the most sensitive and specific of all treponemal tests.…”
Section: Introduction: Forms Of Expressed R-tp Antigensmentioning
confidence: 99%
See 1 more Smart Citation